Caregiving in Times of Uncertainty: Helping Adult Children of Aging Parents Find Support during the COVID-19 Outbreak. Issue 6 (2nd October 2020) - Lightfoot, Elizabeth; Moone, Rajean P.
ABSTRACT: The COVID-19 pandemic, which is especially dangerous to older people, has disrupted the lives of older people and their family caregivers. This commentary outlines the adaptive and emerging practices in formal supportive services for family caregivers, the changing types of support that family caregivers are providing to their older relatives, and the ways family caregivers are seeking informal caregiving support during the COVID-19 outbreak.